Analytical and evaluation Study to the result of higher education studies of all branches (Bio- Tech- hum): to the year (2017-2018) - Sikhi, Abdul Hussain Ganem; Hussain, Thuraya Ali (Al-Adab Journal, 2020)
The Scoundar High School is Considered as the last stage of general Education in Iraq. it is transitionally stage to higher Education, therefore it is very important to draw the policy of higher Education for distribution of stadents at higher institutes or Colleges such as College of medicine, Engineering or pure sciences Colleges and Humani lies.The problem of this research is there are no analytical and evaluation studies for student achievement at final examination of high School in iraq, and there are no Standard norms to Compared with inarder to Know the effectiveness of high School out come.The Importante of this study is concederd as the first attempt to Study and evaluate high School outcome and to establish standard norms that can be used to compare between the outcome of coming years.The procedure of this research was to Collect, tabulate and statisically analyze data. Granghes and tables have been arranged to calculate Stadard for Comparison.The result has shown the student achievement in all the three branches (Bio- Tech- hum) Studies were unacceptable.The Percentage of Passing Student less than (50%) and the overall meen less the (80) while Students grades were Scattered and dose not fit with normal curve. The Students From those who are above average are less than 40%.From this result we can conclude that quality and quantity of high School is not acceptable.The researchers reccomndations are, the staderd norms of this research be used for Comparison in future studies for Ministry of Education should study the Factors that are behind this unacceptable result. This Kind of evaluation Studes Should be performed every year and finaly standard examination Should be Used with machine grading to minimize Humans errors.